Major Histocompatibility Complex Binding, Eluted Ligands, and Immunogenicity: Benchmark Testing and Predictions - Paul, Sinu; Grifoni, Alba; Peters, Bjoern; Sette, Alessandro (Frontiers in Immunology, 2020)
Anti-Drug-Antibody (ADA) responses impact drug safety, potency, and efficacy. It is generally assumed that ADA responses are associated with HLA class II-restricted CD4+T cell reactivity. While this review does not address ADA responses per se, since the analysis presented here are relevant to the topic, because, measuring and/or predicting CD4+ T cell reactivity is a common strategy to address ADA and immunogenicity concerns. Since Human CD4+ T cell reactivity relies on the recognition of peptides bound to HLA class II, prediction and/or measurement of the capacity of different peptides to bind or be natural ligands of HLA class II is used as a predictor of CD4+ T cell reactivity and ADA development. Thus, these three different interconnected variables are commonly utilized in predicting T cell reactivity: MHC binding, capacity to be generated as natural HLA ligands and T cell immunogenicity. To provide the scientific community with guidance in the relative merit of different approaches, it is necessary to clearly define what outcomes are being considered. Thus the accuracy of HLA binding predictions varies as a function of what is the outcome predicted, being it binding itself, natural processing or T cell immunogenicity. Furthermore, it is necessary that the accuracy of prediction is based on rigorous benchmarking, grounded by fair, objective, transparent and experimental criteria. In this review, we provide our perspective on how different variables and methodologies predict each of the various outcomes and point out knowledge gaps and areas to be addressed by further experimental work.